Trabalho e família: Articulações possíveis - Bilac, Elisabete Dória [UNESP] (Departamento de Sociologia da Faculdade de Filosofia, Letras e Ciências Humanas da Universidade de São Paulo, 2014)
This article explores work-family integration, taking into account, on one hand, the way in which this discussion has transformed conceptually over time since the 1970s and, on the other, the empirical observation of the persistence of a model based on overburdening women and relatively low male participation in reproduction. The text discusses the extent to which this persistence derives from a specific combination of demographic and socioeconomic elements and the failure of the few work-family integration policies existing in Brazil to provide widespread access.

Este artigo analisa a articulação trabalho-família levando em conta, de um lado, o modo como tal discussão transformou-se conceitualmente ao longo do tempo desde os anos de 1970 e, de outro, a constação empírica da permanência de um modelo que repousa na sobrecarga feminina e na menor participação masculina na reprodução. Discute-se em que medida essa permanência se deve à combinação particular de elementos demográficos e socioeconômicos e ao fato de que as poucas políticas existentes de articulação trabalho-família em nosso país não permitem acesso generalizado.
Work and family: possibilities for integration
Keywords: Trabalho doméstico; Cuidado; Queda da fecundidade; Envelhecimento populacional; Participação feminina no mercado de trabalho; Domestic work; Care; Decline in fertility; Aging population; Female participation in the care work market